PEMANFAATAN E-GOVERNMENT PADA DESA WONOKARTO UNTUK MENINGKATKAN AKURASI DAN INFORMASI POTENSI DESA - Eviana Septiana Rachman; Beni Noviyanto (Jurnal TAM (Technology Acceptance Model), 2017)
E-government at the village Wonokarto a web-based electronic governance aimed at improving the quality of government services to publik. Development e-government is an effort to develop an electronic-based management government in order to improve the quality of public services effectively and efesien.Wonokarto a village be in the district Gadingrejo Pringsewu Lampung regency. During the service in the village Wonokarto still use manual methods so that the public service of information Wonokarto village less than optimal, with this then to solve it in create a new system that could help the government apparatus Wonokarto village in providing information to the public. The process of creation of e-government at the village Wonokarto is done by analyzing analyzing the existing system in the village of Wonokarto, then making a couple of diagrams, namely, DAD (Data Flow Diagrams), DFD (Data Flow Diagram) and Flowchart. Followed by the web designing and database My SQL .E-Government on Wonokarto village is expected to help government personnel in making the letter and provide services to the community and the right information quickly so that people who want to get information, services and potential Wonokarto Village can access via the Internet.